Histological Evaluation of Cassava Starch/Chicken Gelatin Membranes (2022)
The use of biopolymers for tissue engineering has recently gained attention due to the need for safer and highly compatible materials. Starch is one of the most used biopolymers for membrane preparation. However, incorporating other polymers into starch membranes introduces improvements, such as better thermal and mechanical resistance and increased water affinity, as we reported in our previous work. There are few reports in the literature on the biocompatibility of starch/chicken gelatin composites. We assessed the in vivo biocompatibility of the five composites (T1–T5) cassava starch/gelatin membranes with subdermal implantations in biomodels at 30, 60, and 90 days. The FT-IR spectroscopy analysis demonstrated the main functional groups for starch and chicken gelatin. At the same time, the thermal study exhibited an increase in thermal resistance for T3 and T4, with a remaining mass (~15 wt.%) at 800 C. The microstructure analysis for the T2–T4 demonstrated evident roughness changes with porosity presence due to starch and gelatin mixture. The decrease in the starch content in the composites also decreased the gelatinization heats for T3 and T4 (195.67, 196.40 J/g, respectively). Finally, the implantation results demonstrated that the formulations exhibited differences in the degradation and resorption capacities according to the starch content, which is easily degraded by amylases. However, the histological results showed that the samples demonstrated almost complete reabsorption without a severe immune response, indicating a high in vivo biocompatibility. These results show that the cassava starch/chicken gelatin composites are promising membrane materials for tissue engineering applications.